Religious and Environmental Values in Ornamental Plants Entrepreneurship - Bahagia Bahagia; Abdul Karim Halim; Leny Muniroh; Rimun Wibowo; Siti Aisyah; Mira Nurhati Abi (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Environmental damage is still uncontrollable, starting from the extinction of plant species, climate change and plant damage and environmental pollution. Ornamental plant business as a form to respond to environmental damage. The purpose of this study is to find ecological or environmental values and economic values in ornamental plant businesses. The research method used is descriptive qualitative research method. Meanwhile, the respondent selection technique as resource person uses purposive technique. The results of the study indicate that the ornamental plant business is an indicator of the implementation of religious values because humans are ordered to manage nature. At the same time ornamental plant business includes efforts to give alms to others because ornamental plants provide freshness and beauty to those who see the plant. In addition, the ornamental plant business also helps to improve the environment, including producing oxygen, so that behavior is classified as religious teachings. In addition, the ornamental plant business is an alternative to support family life during the COVID-19 pandemic because ornamental plant cultivation does not need to use large areas of land. Ornamental plant businesses can take advantage of home gardens as a form of responding to narrow land but can still realize sustainable agriculture. At the same time helping people who were laid off from work to choose an ornamental plant business.